Sul presente neoindoario a doppio verbo finito (Atti del Sodalizio Glottologico Milanese, 2019)
The present paper deals with the problem of the origin of a type of “double-finite” periphrasis having the structure, e. g., IS WALKS = ‘walks’ – i.e., formed by a finite form of the ‘be’ auxiliary plus a finite form of the main verb – which is used to express the present tense in a series of New Indo-Aryan languages (including Gujarati and some varieties of the Hindi area). According to the hypothesis proposed here, the appearance of these constructions is related to the grammaticalization of the opposition between the presence and the absence of the copula as a means of distinguishing between different tense-aspect categories. This grammaticalization arose in the course of the diachronic development of predicate constructions involving participles, in which a copula could be included or not. As this paper tries to show, there is, indeed, a fundamental structural analogy between some Hindi and Marathi participle-based periphrases and the “double-finite” present. KEYWORDS: verbal inflection, auxiliary, Indo-Aryan languages, grammaticalization, tense-aspect categories